SARS-CoV-2-associated multisystem inflammatory syndrome in a child - N.M. Nagovitsyna (LCC «Medicine-Inform», 2021)
N.M. Nagovitsyna Kama Children's Medical Center, Naberezhnye Chelny, Russian Federation The COVID-19 infection occurs much less commonly in children than in adults, presumably due to the predominance of asymptomatic variants. Nevertheless, single deaths by the COVID-19 were reported in children worldwide. Some of these deaths result from multisystem inflammatory syndrome (MIS) that develops at late stages or after the COVID-19. MIS is characterized by acute onset, steady fever, skin and mucosal damage, and multiorgan failure. Unlike the classic variant of Kawasaki disease, MIS is associated with more frequent shocks and a more severe course. This paper addresses a case report of MIS with a favorable course and outcome in a 7-year-old boy. Practitioners should be aware that severe intoxication and inflammation with increased inflammatory markers emerging at late stages or after respiratory infections are potential manifestations of MIS. In these cases, tests for the COVID-19 should be timely performed; if found, pathogenic therapy is promptly init iated. Taking into account the insufficient knowledge of the pathogenesis and the knowledge of the consequences of MIS associated with SARS-CoV-2, long-term follow-up monitoring is required. Keywords: coronavirus infection, COVID-19, SARS-СoV-2, multisystem inflammatory syndrome, Kawasaki-like syndrome, Kawasaki-like disease. For citation: Nagovitsyna N.M. SARS-CoV-2-associated multisystem inflammatory syndrome in a child. Russian Journal of Woman and Child Health. 2021;4(4):375-377 (in Russ.). DOI: 10.32364/2618-8430-2021-4-4-375-377.